Comparing Formation or Non-Formation of Bladder Flap at Cesarean Section on Perioperative and Postoperative Complications: Double-Blind Clinical Trial - Farideh Akhlaghi; Azadeh Khazaie; Fateme Jafaripour (Tehran University of Medical Sciences, 2018)
Objective: To investigating formation or non-formation of bladder flap at Cesarean section on the complications during and after surgery. Materials and methods: This is a double-blind clinical trial study conducted during February 2014 to May 2015 on 64 pregnant women with gestational age of 36 weeks or more who were delivered by Cesarean section for the first time. They were randomly divided into two groups (intervention group: non-formation of bladder flap; control group: formation of bladder flap). The time to cut out the baby by Cesarean section, total duration of operation, bladder injury, intraoperative bleeding, hematocrit changes expected prior to during and following operation, postoperative pain, macroscopic and microscopic hematuria, postoperative complications and duration of  hospitalization were compared between two groups. The data were analyzed with SPSS version 16 using and statistics tests. p < 0.05 was considered significant. Results: Time to cut out the baby for the intervention group (124.9 ± 40.5 seconds and for control group 155.1 ± 42.9 seconds) and total duration of the operation (intervention group: 27.7 ± 5.2 min and control group: 34 ± 4.73 min) were significantly different (p = 0.000). Number of gauze consumption during operation and postoperative hematocrit drop in the intervention group was significantly lower in the intervention group compared the control group (p = 0.000). The postoperative pain score in the intervention group (4.8 ± 1.1) and in control group (6.3 ± 0.9) were significantly different (p = 0.000). Conclusion: Omission of the bladder flap at Cesarean section leads to short-term benefits such as reducing the time to cut out the fetus, duration of surgery, decreasing postoperative bleeding and lowering pain.